Controlling selectivity in the rhodium-catalysed intermolecular hydroacylation reaction - Pawley, R (2012)
This thesis explores the area of the intermolecular hydroacylation reaction, catalysed by rhodium diphosphine complexes. A range of latent low-coordinate rhodium diphosphine complexes have been synthesised, and their catalytic activity for the hydroacylation reaction has been investigated. In particular, emphasis has been placed on understanding how subtle changes in diphosphine steric properties affect, and can be used to control, selectivity of this catalysis. Chapter 2 presents investigations into rhodium complexes incorporating the potentially hemilabile P-O-P ligands: POP’, XANTphos and Xphos. The resulting complexes have been fully characterised and their activity for the catalytic intermolecular hydroacylation of aldehyde I (HCOC₂H₄SMe) and alkene II (H₂C=CHCO₂Me) established and compared to the DPEphos system. Further reactivity of Xphos for aromatic aldehyde V (HCOC₆H₄SMe) and alkene II, and aldehyde V and alkyne XI [HC≡CC₆H₃(CF₃)₂] has also been explored, and compared with the catalytic activity of {Rh(PPh₃)₂}⁺. Focus moved from potentially hemilabile ligands to chelating diphosphine ligands of the type PPh₂(CH₂)nPPh₂ (where n = 2-5), and then on to ortho-substituted bulky analogues of the type P(₀-C₆H₅R)₂(CH₂)₂P(₀-C₆H₅R)₂ (where R = Me and ⁱPr) complexed to rhodium. Chapter 3 outlines the complexes synthesised, and their activity for the catalytic intermolecular hydroacylation of aldehyde I and alkene II, aromatic aldehyde V and alkene II or aldehyde V and alkyne XI. Possible explanations for the observed switch in selectivity from alkene to aldehyde hydroacylation, and linear alkyne to branched alkyne hydroacylation, have been explored and are detailed. The final chapter concerns the structure of an interesting catalytic intermediate: the branched alkenyl species for the {Rh(DPEphos)}+ catalysed hydroacylation of aldehyde V and alkyne XI. Investigations into the kinetic and catalytic behaviour of this system were carried out, and a reaction scheme has been proposed which correlates well with kinetic modelling undertaken by Prof. Guy Lloyd-Jones of the University of Bristol.